Reduction in pain response by combined use of local lidocaine anesthesia and systemic ketoprofen in dairy calves dehorned by heat cauterization - Duffield, Todd F. (Canadian Veterinary Medical Association, 2010)
This study assessed the efficacy of ketoprofen for mitigating pain following dehorning with an electric cautery iron. Forty Holstein heifer calves, 4 to 8 wk of age, were randomized to receive a lidocaine cornual nerve block and either an injection of ketoprofen (3 mg/kg IM) or physiological saline, 10 min prior to dehorning. Cortisol was measured from serum obtained 10 min prior to dehorning and at 3 and 6 h post-dehorning. Calf behavior was video-recorded between 0 to 2, 3 to 5, and 6 to 8 h post-dehorning, and frequency of ear flicks, head shakes, head rubs, lying, standing, feeding, and grooming were recorded. Finally, 24-h intake of calf starter was recorded. There was no effect of treatment on cortisol (P > 0.1); however, ketoprofen-treated calves displayed less ear-flicks and total head behavior (P < 0.05), and tended to consume more starter (P = 0.09) than control calves. Ketoprofen is effective for mitigating behavioral effects of postsurgical pain following dehorning in 4- to 8-week-old calves.